(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The discussion in the paper illustrates an integral role of Language for an individual and in the community to communise a socio-economic identity on the one hand, and a shareable method of communication for personal growth on the other. No other option is so effective as Language of communication, which deals with and represents psychological behaviour of an individual. How a meaning becomes understandable in certain situation signifies the role of psychological relevance with Language used.